Chapter 2 A Distinct Role For Parliamentary Administrations In Presidential And Parliamentary Systems? - Christiansen, Thomas; GRIGLIO, Elena; Lupo, Nicola (Taylor & Francis, 2023)
Gradually emerged in England in the aftermath of the struggle between the House of Commons and the Crown, parliamentarism has widely circulated abroad, has been praised by many for its alleged capacity to resist authoritarianism, and is mainly concentrated in Europe as well as in former UK colonies. Likewise, presidentialism, originated for the ﬁrst time from the US Constitution of 1787, is not a monolithic category. Committees, in particular the permanent ones, have famously been labelled as the "backbones" of legislatures. In law-making, the strength of committees is what deﬁnes the strength of a parliamentary institution, in terms of capacity to shape the content of legislation and to oversee the executive. In presidential regimes, the capacity of the Parliament to inﬂuence the budget seems higher, also due to the lack of conﬁdence votes to be used by the executive as a leverage to pressure the legislature on budgetary procedures.